Infracommunities of Streblidae and Nycteribiidae (Diptera) on bats in an ecotone area between Cerrado and Atlantic Forest in the state of Mato Grosso do Sul - Dornelles,Guilherme D. P. (2017)
ABSTRACT We described infracommunities, prevalence and mean intensity of infestation of ecotoparasite flies (Nycteribiidae and Streblidae) on bats in an ecotone area of Cerrado as predominant vegetation, with influence of Atlantic Forest, in the southeast of Mato Grosso do Sul. In 36 sampling nights between April 2015 and August 2016 (23,328 m².h), we captured 17 bat species, of which ten were infested, and 14 species of fly. The most abundant bats were the phyllostomids Artibeus planirostris (Spix, 1823), Glossophaga soricina (Pallas, 1776) and Carollia perspicillata (Linnaeus, 1758) and the most abundant flies were the streblids Trichobius longipes (Rudow, 1871), T. joblingi Wenzel, 1966 and Megistopoda aranea (Coquillett, 1899). Phyllostomus hastatus (Pallas, 1767) was the bat species that presented the highest infestation rate. Platyrrhinus lineatus (É. Geoffroy, 1810) and Desmodus rotundus (É. Geoffroy, 1810) were not infested. Besides that, the frequency of bats that were infested by a single species of fly was higher than the frequency of bats infested for two or more, and it may be a pattern.